Return to Productivity Projections for Individuals With Moderate to Severe TBI Following Inpatient Rehabilitation: A NIDILRR TBIMS and CDC Interagency Collaboration. Issue 2 (March 2020) - Pretz, Christopher; Kowalski, Robert G.; Cuthbert, Jeffrey P.; Whiteneck, Gale G.; Miller, A. Cate; Ketchum, Jessica M.; Dams-O'Connor, Kristen
Abstract : Objective: Return to work and school following traumatic brain injury (TBI) is an outcome of central importance both to TBI survivors and to society. The current study estimates the probability of returning to productivity over 5 years following moderate to severe brain injury. Design: A secondary longitudinal analysis using random effects modeling, that is, individual growth curve analysis based on a sample of 2542 population-weighted individuals from a multicenter cohort study. Setting: Acute inpatient rehabilitation facilities. Participants: Individuals 16 years and older with a primary diagnosis of TBI who were engaged in school or work at the time of injury. Main Outcome Measures: Participation in productive activity, defined as employment or school, as reported during follow-up telephone interviews at 1, 2, and 5 years postinjury. Results: Baseline variables, age of injury, race, level of education and occupational category at the time of injury, disability rating at hospital discharge, substance abuse status, and rehabilitation length of stay, are significantly associated with probability of return to productivity. Individual-level productivity trajectories generally indicate that the probability of returning to productivity increases over time. Conclusions: Results of this study highlight the importance of preinjury occupational status and level of education in returning to productive activity following moderate to severe TBI. Abstract : Supplemental Digital Content is Available in the Text.